1997
DOI: 10.1002/cjce.5450750606
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic fluid flow in irregular eccentric annuli due to axial motion of the inner pipe

Abstract: Fully developed axial laminar flow of viscoplastic Herschel-Bulkley fluids in eccentric annuli between two pipes has been investigated numerically. The pipes are closed at one end and flow is due to the axial motion of the inner pipe. The annuli may be filly open or partially blocked. General non-orthogonal, boundary-fitted curvilinear coordinates have been used to accurately model the irregular annular geometry due to the presence of a flow blockage. A computer code has been developed using a second-order fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Furthermore, due to gravity there will be a strong tendency for the cuttings to accumulate in this region, forming a bed of settled cuttings or a partial obstruction of the annular space between the drill string and the formation. [8] Solids accumulating in this region hinder and can even interrupt the drilling process. [9] To suppress the accumulation of more solids, knowledge of the flow patterns in eccentric and partially-obstructed annuli is essential for the design and operation of these wells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to gravity there will be a strong tendency for the cuttings to accumulate in this region, forming a bed of settled cuttings or a partial obstruction of the annular space between the drill string and the formation. [8] Solids accumulating in this region hinder and can even interrupt the drilling process. [9] To suppress the accumulation of more solids, knowledge of the flow patterns in eccentric and partially-obstructed annuli is essential for the design and operation of these wells.…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming these setbacks, Mitsoulis et al proposed a new HB stress function based on Papanastasiou idea on Bingham type materials for a large but finite apparent viscosity value at vanishing shear rate as trueτtrue‾=K|γ˙|n1+τ01exp(m|γ˙|)|γ˙|trueγ˙true‾, where the regularization parameter m is a large number to guarantee large apparent viscosity at vanishing rate‐of‐strain at a value of mτ0+K|γ˙|(n1)). This model has been implemented in various numerical modelling for HB fluids …”
Section: Introductionmentioning
confidence: 99%
“…The model has been extensively validated against field data (Wagner et al 1993;Robello et al 2001;Rommetveit et al 2004). A recently numerical study (Hussain and Sharif 2009) indicated the reduction of surge pressure with the increase in eccentricity. For a partially blocked eccentric annulus with cuttings bed, the surge pressure decreases with the increase in the bed thickness.…”
Section: Literature Reviewmentioning
confidence: 99%